2019
DOI: 10.5694/mja2.50383
|View full text |Cite
|
Sign up to set email alerts
|

Right care, first time: a highly personalised and measurement‐based care model to manage youth mental health

Abstract: This supplement was sponsored by 2 S3 Right care, fi rst time: a highly personalised and measurement-based care model to manage youth mental health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
157
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 415 publications
(484 reference statements)
4
157
1
2
Order By: Relevance
“…However, there are clear areas for improvement in meeting the needs of young people attending EISs for FEP, and alternative models should be explored. Transdiagnostic approaches, such as clinical staging models, may reduce the potential for disengagement processes that are shown to occur due to a mismatch between the person and diagnostically driven approaches (24)(25)(26)(27). Clinical staging models comprise of stages ranging from stage 0 (asymptomatic individuals at risk of mental illness) through to stage 4 (severe, persistent, and unremitting illness).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are clear areas for improvement in meeting the needs of young people attending EISs for FEP, and alternative models should be explored. Transdiagnostic approaches, such as clinical staging models, may reduce the potential for disengagement processes that are shown to occur due to a mismatch between the person and diagnostically driven approaches (24)(25)(26)(27). Clinical staging models comprise of stages ranging from stage 0 (asymptomatic individuals at risk of mental illness) through to stage 4 (severe, persistent, and unremitting illness).…”
Section: Discussionmentioning
confidence: 99%
“…These early phases are characterized by changes in social behaviors and difficulties participating in work and study 5 , both of which are reflected in the high rates of functional impairment at presentation to youth-specific services 6,7 . As functional trajectories are heterogeneous and often persistently impaired 6 , there is a critical need for identification of factors associated with functional course which may guide interventions to those at risk of enduring and lifelong functional disability 8 .…”
Section: Introductionmentioning
confidence: 99%
“…All of these elements are necessary for the delivery of the highly personalised and measurement‐based care model we propose in the Supplement that accompanies this issue of the MJA . Although this novel, technology‐enabled care model for youth mental health has many evidence‐based components and has been co‐designed with young people and their families, as seen in the Project Synergy trials, it remains to be demonstrated whether, compared with either existing child and adolescent or adult service models, it results in improved clinical and social outcomes.…”
mentioning
confidence: 99%
“…The highly personalised component is achieved through the integration of three core concepts: assessing multidimensional domains of morbidity and function; clinical staging; and mapping pathophysiological pathways across development, from childhood, through adolescence and into early adulthood, as well as illness trajectories. The measurement‐based care component is achieved by linking individual care to the use of more sophisticated real‐time health information technologies that can enhance immediate and continuous clinical decision‐making (see Chapter 5 of the accompanying Supplement) …”
mentioning
confidence: 99%
See 1 more Smart Citation